Protocol for a qualitative study of knowledge translation in a participatory research project - Lillehagen, Ida (BMJ Publishing Group, 2013)
INTRODUCTION: In this article, we present a methodological design for qualitative investigation of knowledge translation (KT) between participants in a participatory research project. In spite of a vast expansion of conceptual models and frameworks for conducting KT between research and practice, few models emphasise how KTs come about. Better understanding of the actions and activities involved in a KT process is important for promoting diffusion of knowledge and improving patient care. The purpose of this article is to describe a methodological design for investigating how KTs come about in participatory research. METHODS AND ANALYSIS: The article presents an ethnographic study which investigates meetings between participants in a participatory research project. The participants are researchers and primary healthcare clinicians. Data are collected through observation, interviews and document studies. The material is analysed using the analytical concepts of knowledge objects, knowledge forms and knowledge positions. These concepts represent an analytical framework enabling us to observe knowledge and how it is translated between participants. The main expected outcome of our study is to develop a typology of KT practices relevant to participatory research. ETHICS AND DISSEMINATION: The project has been evaluated and approved by the Norwegian Social Science Data Services. Informed consent was obtained for all participants. The findings from this study will be disseminated through peer-reviewed publications and national and international conference presentations.